Gastos com gestão ambiental nas capitais brasileiras e a relação com a qualidade de vida - Maia, Leonardo Aguiar (2015)
The environment has always been exploited by humans, carefree and mischievous way, intending to take advantage of what had and without understanding that resources could be finite. The man thought that nature offered inexhaustible raw material. However, the reality has changed and showed that maintaining the levels of consumption, exploitation of natural resources and energy use would lead to environmental degradation of high proportions, irreversible, leading to uncertainty about the future of humanity. Thus arose the concept of sustainable development, which allows the use of natural resources to provide quality of life, but without committing to use these resources for future generations. Thus, proposals have emerged to measure quality of life and measure sustainable development as a fundamental instrument for the formulation of public policies. In this context, public expenditure is undertaken in order to achieve government objectives through public policies that directly impact the society to social welfare. The focus of this study is on public spending at the municipal sustainable development index and the population's quality of life. The overall objective of the research was based on analyzing the influence of the costs incurred by the Brazilian capital in the population's quality of life. The methodology used was characterized as exploratory, descriptive, based on bibliographical and documentary research procedures. Sets up a quantitative data approach, guided by linear regression analysis seeking to explain the relationship between the variables Municipal Sustainable Development Index (IDSM), dependent, and spent on environmental management function, independent. The research population is made up of Brazilian state capitals, opting for the temporal cut 2010 to 2013. There was a larger application of low resources, the total executed budget expenditure, with the budgetary tool "environmental management" in relation to the total executed budget. The result of the linear regression showed that the IDSM is explained by expenses incurred in the budget environmental management function. We conclude, therefore, that the expenditure carried out by the Brazilian capitals in the budget environmental management function positively influences the population's quality of life, given that the higher the amount realized, the greater the IDSM used as the quality of life parameter.